2003
DOI: 10.1890/0012-9658(2003)084[0362:ibfasb]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Interactions Between Fire and Spruce Beetles in a Subalpine Rocky Mountain Forest Landscape

Abstract: Interactions between natural disturbances are widely recognized as important determinants of vegetation patterns in forested landscapes but have only rarely been investigated quantitatively. In a subalpine forest landscape in northwestern Colorado, we quantified spatial associations of fire and spruce beetle (Dendroctonus rufipennis) outbreaks over more than a century and developed a multivariate logistic model of probability of occurrence of spruce beetle outbreaks. The study area, an ∼2800 km2 landscape in W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
128
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 143 publications
(134 citation statements)
references
References 29 publications
4
128
1
Order By: Relevance
“…Colorado (Bebi et al 2003, Kulakowski andVeblen 2007) and in conifer forests of California (Bond et al 2009), which generally do not support the hypothesis of increased probability of stand-replacing crown fire following bark beetle outbreak. Similarly, in lodgepole pine forests, Kulakowski and Veblen (2007) did not find higher occurrence or severity of fire in 5-year post-beetle stands.…”
Section: Relationship To Other Studiesmentioning
confidence: 78%
See 1 more Smart Citation
“…Colorado (Bebi et al 2003, Kulakowski andVeblen 2007) and in conifer forests of California (Bond et al 2009), which generally do not support the hypothesis of increased probability of stand-replacing crown fire following bark beetle outbreak. Similarly, in lodgepole pine forests, Kulakowski and Veblen (2007) did not find higher occurrence or severity of fire in 5-year post-beetle stands.…”
Section: Relationship To Other Studiesmentioning
confidence: 78%
“…These studies, which were carried out in different forest types (lodgepole pine [ (Simard et al 2008), with some analyses suggesting slightly increased probability or severity of fire following beetle outbreak (Bigler et al 2005), and others showing no evidence for such a relationship (Bebi et al 2003). In this study, we employ a prospective approach to quantify fuel dynamics and predict potential fire behavior during and for several decades after bark beetle outbreak.…”
Section: Introductionmentioning
confidence: 99%
“…Fires , hurricanes (Boose et al 1994), and blowdowns (Canham and Loucks 1984, Foster and Boose 1992, Rich et al 2007) have garnered widespread attention, but ice storms, floods, volcanic eruptions, tornados, and insects are stimulating increased interest (cf. Foster et al 1998, Bebi et al 2003, Stueve et al 2007.…”
Section: Introductionmentioning
confidence: 99%
“…Models of such interactions mainly focused on descriptive, statistical approaches, including various logistic regression models (Bebi et al, 2003;Bigler et al, 2005;Breece et al, 2008), generalized linear models with different link functions (Peltonen, 1999;Eriksson et al, 2005;Hood and Bentz, 2007) and classification tree models (Kulakowski and Veblen, 2007). As an alternative approach for evaluating hypotheses and conceptual understanding about fire-bark beetle interactions, Youngblood et al (2009) demonstrated the utility of structural equation modelling.…”
Section: Interactions With Other Disturbance Agentsmentioning
confidence: 99%